Draft Sixth Five Year Plan 1980-85 and Annual Plan 1981-82 Volume-I Government of Kerala - Planning Commission (Planning Commission, 1980)
Since the formation of Kerala nearly 25 years ago successive Governments in the State have generally followed a welfare approach to development The spread of education and health services started by the earlier princely states was intensified and also extended to the Malabar area Since the birth of the State coincided the coming into power of political parties with progressive ideologies, the demands of organised sections were given sympathetic consideration Over the years, several welfare measures for the old the unorganised workers and the unemployed have been initiated As a result of all this, investment in human capital measured by levels of literacy, education, health services, water supply and so on, is the highest in Kerala in the country.
State Planning Board Trivandrum